High initial IgG antibody levels against Orientia tsutsugamushi are associated with an increased risk of severe scrub typhus infection. - Carol S Devamani; John A J Prakash; Neal Alexander; William Stone; Karthik Gunasekaran; Winsley Rose; Wolf-Peter Schmidt (Public Library of Science (PLoS), 2021)
Background Scrub typhus is a dominant cause of febrile illness in many parts of Asia. Immunity is limited by the great strain diversity of Orientia tsutsugamushi. It is unclear whether previous infection protects from severe infection or enhances the risk. Methods/principal findings We studied IgG antibody levels against O. tsutsugamushi at presentation in 636 scrub typhus patients using enzyme-linked immunosorbent assays (ELISA). The association between ELISA optical density (OD) and risk of severe infection was modelled using Poisson regression. OD was categorised as low (<1.0), intermediate (1.0 to 2.9), and high (≥3.0). OD was also modelled as a continuous variable (cubic spline). Median age of cases was 41 years (range 0-85), with 37% having severe infection. Compared to the low category, the age-adjusted risk of severe infection was 1.5 times higher in the intermediate category (95%CI 1.2, 1.9), and 1.3 times higher in the high category (95%CI 1.0, 1.7). The effect was stronger in cases <40 years, doubling the risk in the intermediate and high categories compared to the low category. The effect was more pronounced in cases tested within 7 days of fever onset when IgG ODs are more likely to reflect pre-infection levels. Conclusions/significance Intermediate and high IgG antibody levels at the time of diagnosis are associated with a higher risk of severe scrub typhus infection. The findings may be explained by severe infection eliciting an accelerated IgG response or by previous scrub typhus infection enhancing the severity of subsequent episodes.